Combined single channel and single molecule detection identifies subunit composition of STIM1-activated transient receptor potential canonical (TRPC) channels. Issue 1 (January 2015) - Asanov, Alexander; Sampieri, Alicia; Moreno, Claudia; Pacheco, Jonathan; Salgado, Alfonso; Sherry, Ryan; Vaca, Luis
Graphical abstract